Music therapy and Sanfilippo syndrome: an analysis of psychological and physiological variables of three case studies - P. Pérez-Núñez; E. Lázaro; I. Amayra; J. F. López-Paz; P. Caballero; O. Martínez; M. Pérez; S. Berrocoso; M. Al-Rashaida; M. García; A. A. Rodríguez; P. M. Luna (Orphanet Journal of Rare Diseases, 2021)
Abstract Introduction Mucopolysaccharidosis type III (MPS III) or Sanfilippo syndrome is a neurodegenerative disease caused by the accumulation of mucopolysaccharides in the body. As the symptoms are wide ranging, it is a challenge to provide a diagnosis and psychological treatment for affected children. Method The main objective of this study was to describe a form of music therapy treatment applied to three children diagnosed with MPS III. The psychological variables were evaluated by an ad hoc observation recording template, and the physiological variables were measured with a digital meter before and after each session. The perception of the parents was also considered through a semi-structured interview. Results An improvement in the psychological variables was shown in all cases. Changes in the physiological variables were also noted, although they varied according to each child. The parents report some benefit of music therapy and they share difficulty in assessing the extent of benefits of the music therapy. Discussion Findings indicate that music therapy can be a useful form of treatment with multiple benefits for children with conditions such as MPS III or similar conditions. However, further research is needed in this area and in the development of specific ways of evaluating music therapy.